x+7-3x=16-5x+3

Simple and best practice solution for x+7-3x=16-5x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+7-3x=16-5x+3 equation:


Simplifying
x + 7 + -3x = 16 + -5x + 3

Reorder the terms:
7 + x + -3x = 16 + -5x + 3

Combine like terms: x + -3x = -2x
7 + -2x = 16 + -5x + 3

Reorder the terms:
7 + -2x = 16 + 3 + -5x

Combine like terms: 16 + 3 = 19
7 + -2x = 19 + -5x

Solving
7 + -2x = 19 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
7 + -2x + 5x = 19 + -5x + 5x

Combine like terms: -2x + 5x = 3x
7 + 3x = 19 + -5x + 5x

Combine like terms: -5x + 5x = 0
7 + 3x = 19 + 0
7 + 3x = 19

Add '-7' to each side of the equation.
7 + -7 + 3x = 19 + -7

Combine like terms: 7 + -7 = 0
0 + 3x = 19 + -7
3x = 19 + -7

Combine like terms: 19 + -7 = 12
3x = 12

Divide each side by '3'.
x = 4

Simplifying
x = 4

See similar equations:

| 1.2x=.72 | | 5x-20+3=7x | | 4=7w+6 | | 4x+6=2(x+8) | | 3x=7x-20 | | 7x-3=5-2x | | 3x-2x+1=x+6 | | 3x+11+7x+3=180 | | 12=3(x-9) | | 3x+5x+10=10x-2x+10 | | 12z^3=14z^2+48z | | 2x+18=4x+10 | | 7-4y=7 | | -9x-5y=27 | | 2*(ln(x))+1=0 | | x-4(x+3)=12 | | 8q+5=2 | | 50q-43=52q-18 | | 250=14w+9g | | 6x-1=7(x+9) | | 2(x-8)=2x+6 | | 2x^2+10X+3=3 | | 4.5g+0.75=18.75 | | 4.5+0.75=18.75 | | 3x=5(x+3)-s | | f(x)=3x^2-9x+6 | | -4=2-3p | | 4k-5=-17 | | -15r+5=50 | | x+4x+(4x-49)=437 | | 5(x-4)+3=7x | | 3x^2-2x-30=0 |

Equations solver categories